2005
DOI: 10.1007/s00425-005-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress alters genes expression and induces ovule abortion: reactive oxygen species appear as ovules commit to abort

Abstract: Environmental stress dramatically reduces plant reproduction. Previous results showed that placing roots in 200 mM NaCl for 12 h caused 90% of the developing Arabidopsis ovules to abort (Sun et al. in Plant Physiol 135:2358-2367, 2004). To discover the molecular responses that occur during ovule abortion, gene expression was monitored using Affymetrix 24k genome arrays. Transcript levels were measured in pistils that were stressed for 6, 12, 18, and 24 h, then compared with the levels in healthy pistils. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…Some researchers showed that a change in cAPX activity is an early event in the PCD process, with a 50% decrease in activity occurring immediately after induction of PCD (Vacca et al 2004;Locato et al 2009). It was also reported that APX genes are down-regulated after ovules commit to abortion (Sun et al 2005). In our study, three protein spots (i.e., spot nos.…”
Section: Proteins Involved In Detoxification Of Rosmentioning
confidence: 87%
“…Some researchers showed that a change in cAPX activity is an early event in the PCD process, with a 50% decrease in activity occurring immediately after induction of PCD (Vacca et al 2004;Locato et al 2009). It was also reported that APX genes are down-regulated after ovules commit to abortion (Sun et al 2005). In our study, three protein spots (i.e., spot nos.…”
Section: Proteins Involved In Detoxification Of Rosmentioning
confidence: 87%
“…Furthermore, Arabidopsis exhibits female reproductive organ abortion because of salt stress (Park et al, 2004;Sun et al, 2004). Another study uncovered altered expression of genes encoding 65 transcription factors in response to salt stress, including 6 ETHYLENE RESPONSE FACTOR (ERF)/AP2-family members and 11 NAC proteins (Sun et al, 2005). However, these studies did not characterize reproductive development.…”
Section: Introductionmentioning
confidence: 91%
“…4B). Thus, we assume that improved resource allocation during seed set and development might have reduced the frequency of ovule abortion, a process that frequently occurs during reproduction, in particular in response to nutrient limitations and environmental stress (Sun et al, 2004(Sun et al, , 2005.…”
Section: Mp17:gfp-mediated Modification Of Suc Efflux Correlates Withmentioning
confidence: 99%